Comparative Study of Macroeconomic Variables and Corporate Bond Issuance Behavior: A Case of Nepal and Bangladesh - Joshi, Badri Prasad; Thapa, Bharat Singh (Apex Journal of Business and Management, 2024)
The primary objective of this study is to investigate how various macroeconomic variables—such as the size of the economy, size of the bank, size of corporate debt, openness of the economy, and exchange rate variability—affect the issuance behavior of corporate debt in Nepal and Bangladesh. Using secondary data collected from the World Bank and respective countries’ official websites spanning 27 years from 1993 to 2019, the research employs an analytical and descriptive research design. Statistical tests, including correlation, regression analysis, and t-tests, were conducted using STATA, SPSS, and Excel. The findings reveal a strong correlation between the size of corporate debt and corporate debt issuance behavior in both Nepal and Bangladesh. T-tests indicate significant differences in the openness of the economy, size of the bank, and issuance behavior of corporate debt between the two countries. Hypothesis testing underscores a significant relationship between the size of corporate debt and the issuance behavior of corporate debt in both Nepal and Bangladesh. This research contributes valuable insights for policymakers, financial analysts, and businesses seeking to navigate the complexities of corporate bond markets in these regions.